The correct answer is zm ( o + c + e) I hope this helps
<h3><u>Ⲁⲛ⳽ⲱⲉⲅ:</u></h3>
- <u>▶( x - 3 ) ( 3x - 6 )</u>
<h3><u>Ⲋⲟⳑⳙⲧⳕⲟⲛ :</u></h3>
ㅤㅤㅤ➙ 3x² - 15x + 18
ㅤㅤㅤ➙ 3x² - 9x - 6x + 18
ㅤㅤㅤ➙ 3x ( x - 3 ) + 6 ( - x + 3 )
ㅤㅤㅤ➙ 3x ( x - 3 ) - 6 ( x - 3 )
ㅤㅤㅤ➙ <u>( x - 3 ) ( 3x - 6 )</u>
5x2-3x=25
Divide each term by 5:
x^2 - 3/5x = 5
Make a trinomial square of the left side by taking the square of half of the coefficient of x.
The coefficient of x is -3, so the square would be (-3/10)^2
Add that to both sides of the equation.
Now you have:
x^2 - 3/5x + (-3/10)^2 = 5 + (-3/10)^2
Simplify both sides:
x^2 -3/5x +9/100 = 509/100
Factor the trinomial:
(x-3/10)^2 = 509/100
Solve for x, , take the square root of both sides:
x-3/10 = +/-√509 / 100
Simplify the right side:
x-3/10 = +/-√509/10
Add 3/10 to both sides:
X = +/-√509/10 + 3/10 ( this is the exact form)
You can then find the decimal answer if needed.